2017
DOI: 10.1016/j.surg.2016.04.054
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative detection of RAS mutation may guide extent of thyroidectomy

Abstract: Background Preoperative detection of RAS mutations can contribute to cancer risk assessment in indeterminate thyroid nodules, although RAS is not always associated with malignancy. Methods Fine-needle aspiration samples classified in 1 of 3 indeterminate cytology categories were prospectively tested for N-, H-, and K-RAS mutations using next-generation sequencing assay. Results In the study, 93 patients with 94 nodules had preoperative RAS detected, of whom 86 patients had an operation (69% total thyroidec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 23 publications
(31 reference statements)
8
63
1
Order By: Relevance
“…Prior studies have shown that RAS mutations have a significant risk of malignancy. One study found that 76% of RAS‐positive indeterminate thyroid nodules were malignant; however, 56% of the RAS‐positive malignant cases were encapsulated FVPTC . RAS mutations are now indicative of a clonal tumor with 80% probability of low risk carcinoma or NIFTP, which are managed by lobectomy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have shown that RAS mutations have a significant risk of malignancy. One study found that 76% of RAS‐positive indeterminate thyroid nodules were malignant; however, 56% of the RAS‐positive malignant cases were encapsulated FVPTC . RAS mutations are now indicative of a clonal tumor with 80% probability of low risk carcinoma or NIFTP, which are managed by lobectomy .…”
Section: Discussionmentioning
confidence: 99%
“…ThyroSeq® v3 was also validated to identify Hürthle cell neoplasms including Hürthle cell adenomas and carcinomas. Clonal CNA is a nonspecific molecular alteration that is specifically associated with Hürthle cell neoplasms . Analysis of global CNA in one study showed significantly different patterns of chromosomal aberrations in HCC compared with PTC or FTC; however, there was no difference in chromosomal aberrations between HA and HCC.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the well‐recognized low interobserver agreement for the classification of noninvasive encapsulated lesions with follicular pattern that have, if at all, very‐low malignant potential, is behind the differences in the prevalence of malignancy of RAS and perhaps other mutations . A recent publication on 94 RAS ‐mutant tumors has also suggested that a lobectomy seems appropriate for these tumors . However, the authors of that study concluded that finding a RAS mutation preoperatively could be used to guide the extent of thyroidectomy .…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, this panel seemed reliable as rule‐out test in follicular neoplasms but not in atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS) . Besides the need to bring the performance of oncogene panels into sharper focus, their role in planning the extent of surgery is controversial and needs to be defined . The 2015 American Thyroid Association (ATA) recommends thyroid lobectomy for solitary, cytologically indeterminate thyroid nodules (ITNs) but suggest that total thyroidectomy may be preferred if a mutation specific for carcinoma is identified, given the higher risk for cancer (recommendation #20) .…”
Section: Introductionmentioning
confidence: 99%
“…1a). 1 Follicular variant PTC comprises mostly low grade tumors and RAS-like tumors [86][87][88][89][90][91][92][93][94][95][96][97] (Table 2). It can be classified into either borderline (WDT-UMP or NIFTP) or malignant (invasive encapsulated PTC or infiltrative PTC) according to the absence of, incomplete or definite capsular/lympho-vascular invasion.…”
Section: Follicular Variant Ptcmentioning
confidence: 99%